Mornova zijalka pri Šoštanju - Brodar, Mitja (Arheološki vestnik, 1996)
The site of Mornova Zijalka was discovered as early as 1935, but only brief information about it was published then. It has since been assumed that it is dated to the end of the Mousterian. This article presents the results of specific analysis of the not very extensive collection of material, and the author has established that it should be classified to the late Paleolithic, and that insufficient arguments exist for dating it to the Aurignacian. The artifacts from upper strata, unpublished to the present, should be classified to the Gravettian. Interesting finds from the surface layers are also noted.